Compromisso da Via Aérea por Hematoma Pós-Tiroidectomia - Jacob, Miguel; Portela, Inês; Gestosa, Sandra; Lares, Ana (Journal of the Portuguese Society of Anesthesiology, 2018)
Compromisso da Via Aérea por Hematoma Pós-Tiroidectomia